Review and cladistic analysis of the Neotropical tarantula genus Ephebopus Simon 1892 (Araneae: Theraphosidae) with notes on the Aviculariinae - West, Rick C.; Marshall, Samuel D.; Fukushima, Caroline Sayuri; Bertani, Rogério (Zootaxa, 2008)
The tarantula genus Ephebopus Simon 1892 is reviewed and includes the type species, E. murinus (Walckenaer 1837), and E. uatuman Lucas, Silva & Bertani 1992, E. cyanognathus West & Marshall 2000, E. rufescens West & Marshall 2000 and Ephebopus foliatus, sp. nov., from Guyana. Ephebopus violaceus Mello-Leitão 1930 is transferred to Tapinauchenius Ausserer, where it is a senior synonym of Tapinauchenius purpureus Schmidt 1995 new synonymy. Ephebopus fossor Pocock 1903 is considered a nomen dubium. Ephebopus occurs in northeastern South America where it is known only from Brazil, Guyana, Suriname, and French Guiana. Spiders of the genus are generally fossorial; however, Ephebopus murinus has a developmental stage that is arboreal. A cladistic analysis of the Theraphosidae retrieves the Aviculariinae as monophyletic, including Avicularia Lamarck, Iridopelma Pocock 1901, Pachistopelma Pocock 1901, Tapinauchenius, Psalmopoeus Pocock, Ephebopus, Stromatopelma Karsch and Heteroscodra Pocock, having as a synapomorphy the well-developed scopulae on tarsi and metatarsi I–II that is very laterally extended.